Interaction of race and pathology for neuroendocrine tumors: Epidemiology, natural history, or racial disparity?. Issue 6 (6th August 2019) - DePalo, Danielle K.; Lee, Rachel M.; Lopez‐Aguiar, Alexandra G.; Gamboa, Adriana C.; Rocha, Flavio; Poultsides, George; Dillhoff, Mary; Fields, Ryan C.; Idrees, Kamran; Nathan, Hari; Abbott, Daniel; Maithel, Shishir K.; et al.
Abstract: Background and Objectives: Although minority race has been associated with worse cancer outcomes, the interaction of race with pathologic variables and outcomes of patients with gastroenteropancreatic neuroendocrine tumors (GEP‐NETs) is not known. Methods: Patients from the US Neuroendocrine Study Group (2000‐2016) undergoing curative‐intent resection of GEP‐NETs were included. Given few patients of other races, only Black and White patients were analyzed. Results: A total of 1143 patients were included. Median age was 58 years, 49% were male, 14% Black, and 86% White. Black patients were more likely to be uninsured (7% vs 2%, P = .011), and to have symptomatic bleeding (13% vs 7%, P = .009), emergency surgery (7% vs 3%, P = .006), and positive lymph nodes (LN) (47% vs 36%, P = .021). However, Black patients had improved 5‐year recurrence‐free survival (RFS) (90% vs 80%, P = .008). Quality of care was comparable between races, seen by similar LN yield, R0 resections, postoperative complications, and need for reoperation/readmission (all P > .05). While both races were more likely to have pancreas‐NETs, Black patients had more small bowel‐NETs (22% vs 13%, P < .001). LN positivity was prognostic for pancreas‐NETs (5‐year RFS 67% vs 83%, P = .001) but not for small‐bowel NETs. Conclusions: Black patients with GEP‐NETs had more adverse characteristics and higher LN positivity. Despite this, Black patients have improved RFS. This may be attributed to the epidemiologic differences in the primary site of GEP‐NETs and variable prognostic value of LN‐positive disease.